TOOLKIT FOR ENSURING SYSTEMIC DEVELOPMENT OF HEALTH CARE INSTITUTIONS IN UKRAINE - KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The research emphasizes the objectively existing need, as well as the problem of ensuring effective management of the systemic development of health care institutions in Ukraine, in particular in the segment of private ownership. The purpose of the study is to determine the scientific substantiation of the theoretical, methodological and applied characteristics of the implementation of the toolkit for ensuring the systemic development of health care institutions in Ukraine, which provides for institutional and structural reforms in the field for the sake of organizations and the constant improvement of the quality of medical care for the population in accordance with international standards. It is shown that every enterprise is an open complex dynamic system that functions in a defined external environment. The modern socio-economic environment is characterized by a high rate of change, which can sometimes be predicted with low probability. Maintaining the existing state of the enterprise and moving forward is possible only under conditions of effective adaptation of the enterprise to changes in the external environment Options for ensuring systemic development of health care institutions, namely, internal growth due to more effective use of own resource potential; redistribution of internal resources, focusing them on progressive types of economic activity; termination of the provision of a number of services that require higher quality resources, in their real absence; transfer of certain types of activities, not provided with resources, to other performers on a contractual basis; merger / acquisition with the aim of improving the system of medical care of the population. The advantages and disadvantages and peculiarities of practical implementation of relevant strategic decisions are indicated. The scientific novelty of the research results lies in the further development of methodological and applied principles of strategic management of the development of health care institutions due to the identification of strategic alternatives for the efficiency of activities, as well as tools and means, the implementation of which ensures systemic development. The applied value of the research results lies in the development of various scenarios for the further balanced development of health care institutions.